Analisa Gross Profit Margin, Net Profit Margin dan Perputaran Kas Terhadap Return on Investment pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2019 - Pradhana Jayasukmana; Danang Djoko Susilo (Jurnal Pajak dan Bisnis, 2022)
This study aims to examine the effect of Gross Profit Margin, Net Profit Margin and Cash Turnover on Return On Investment in Manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The source of data in this study is secondary data in the form of financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The data collection technique for this research is data accessed through the website www.idx.co.id. The results of this study indicate that partially based on the T test gross profit margin, net profit margin and cash turnover have a positive and significant effect on return on investment. Simultaneously based on the F test gross profit margin, net profit margin and cash turnover simultaneously affect the return on investment. Based on the results of the analysis of the correlation coefficient and the coefficient of determination shows that the relationship between gross profit margin, net profit margin, cash turnover and return on investment is very strong and most of the return on investment is influenced by the three independent variables.